Evaluation of Stability of Complexes of Inner Transition Metal Ions with 2-Oxo-1-pyrrolidine Acetamide and Role of Systematic Errors - Sangita Sharma; Jayesh Ramani; Dhara Patel; Ketan Patel; Mahesh Kadiya (E-Journal of Chemistry)
BEST FIT models were used to study the complexation of inner transition metal ions like Y(III), La(III), Ce(III), Pr(III), Nd(III), Sm(III), Gd(III), Dy(III) and Th(IV) with 2-oxo-1-pyrrolidine acetamide at 30 °C in 10%, 20, 30, 40, 50% and 60% v/v dioxane-water mixture at 0.2 M ionic strength. Irving Rossotti titration method was used to get titration data. Calculations were carried out with PKAS and BEST Fortran IV computer programs. The expected species like L, LH+, ML, ML2 and ML(OH)3, were obtained with SPEPLOT. Stability of complexes has increased with increasing the dioxane content. The observed change in stability can be explained on the basis of electrostatic effects, non electrostatic effects, solvating power of solvent mixture, interaction between ions and interaction of ions with solvents. Effect of systematic errors like effect of dissolved carbon dioxide, concentration of alkali, concentration of acid, concentration of ligand and concentration of metal have also been explained here.